2020
DOI: 10.33314/jnhrc.v18i1.2629
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 in Nepal

Abstract: The novel coronavirus COVID-19 (SARS-CoV-2) was first reported on 31 December 2019 in Wuhan City, China. The first case of COVID-19 was officially announced on 24 January, 2020, in Nepal. Nine COVID-19 cases have been reported in Nepal. We aim to describe our experiences of COVID-19 patients in Nepal.Keywords: COVID-19; experience; Nepal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…This prevalence also might not represent national level prevalence as samples from random populations have not been tested. Early studies reported that COVID-19 patients in Nepal showed few or no symptoms at all (24,36). The situation updates of the Ministry of Health and Population (MoHP) also indicates that most of the confirmed cases are found through active surveillance and contact tracing rather than patients visiting hospitals with symptoms (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence also might not represent national level prevalence as samples from random populations have not been tested. Early studies reported that COVID-19 patients in Nepal showed few or no symptoms at all (24,36). The situation updates of the Ministry of Health and Population (MoHP) also indicates that most of the confirmed cases are found through active surveillance and contact tracing rather than patients visiting hospitals with symptoms (25).…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of cases have been reported from India, Bangladesh, and Indonesia (23). In Nepal, the first case of COVID-19 was officially reported on 23rd January 2020 in a 32-year-old man who returned from Wuhan, China (24). The second case was detected after two months on 23rd March.…”
Section: Introductionmentioning
confidence: 99%
“…The case was a male individual who was 32 years in age and was a citizen of Nepal who was studying in Wuhan. He returned to Nepal for a winter vacation on January 9, 2020 [ 17,18]. The throat swab was sent to Hongkong and was found to be COVID-19 positive on January 25, 2020 [19].…”
Section: Timeline Of Covid-19 In Nepalmentioning
confidence: 99%
“…The indexed case was found on 23 January 2020 in Kathmandu on a person who had travelled from Wuhan, China [5]. The second case was confirmed two months later on 23 March who had travelled to Nepal from France via Qatar [6].…”
Section: Introductionmentioning
confidence: 99%